CURRENT TRENDS OF DIRECT FOREIGN INVESTMENT IN THE WORLD - A. Panzabekova; M. Kolbayev; G. Nyurlikhina; S.Velesсo (Scientific Journal of Pedagogy and Economics, 2019)
The purpose of the article is to identify the world trends in the movement of foreign direct investment (FDI) in modern conditions. The methodology of the research has made general scientific principles of cognition of economic phenomena - dialectical, concrete historical, systemic approaches. The research used such scientific methods as analysis and synthesis, comparison, generalization, as well as methods of economic and statistical analysis. The information basis for the study was the annual World Investment Reports of the United Nations Conference on Trade and Development (UNCTAD). The article analyzes the dynamics of FDI in certain periods from 1982 to 2016, the results of which showed an ambiguous fluctuation in their volumes. The analysis of the sectoral structure of FDI on which the main motive of foreign investments was determined at the beginning of the period under review was access to natural resources. The geographic structure of FDI in the world is studied. The author analyzes the data on FDI in the context of developed, developing countries and countries with economies in transition, in order to identify the activity and role of groups of countries with different economic development in the processes of direct foreign investment, and to determine the structural shifts in the geography of FDI in recent decades. Thus, it was revealed that the lion’s share of FDI is in developed countries, but their share decreases slightly each year in favor of developing countries. Also, the article reveals the trends regarding investment policies of countries, which are the desire of many states to encourage, simplify and liberalize investments.